Common lands and customary law: institution change in North India over the past two centuries - Chakravarty- Kaul, Minoti (Delhi, 1996)
In 1978 villagers in Kanjhawala agitated against the partition and parcelling of their common lands among the landless by the Delhi administration. Common Lands and Customary Law delves into the past to dispel the negative images of this rural protest built up by the media and by the authorities. The author argues that communally held resources are not necessarily open to misuse and private exploitation, and that the "tragedy of the commons" is not inevitable. For this purpose she examines hundreds of court disputes in greater Punjab, an area which includes present-day Pakistan, over the past two centuries. These court disputes highlight the role of customary law and institutions of property rights devised by rural communities to induce cooperation among individuals and to discourage free-riding or cheating in the use of resources held in common. This book will interest environmental, agrarian and economic historians, and development economists. Minoti Kaul's conclusions about the role of customary law in the governing of common property resources will be of significance to policy-makers and non-governmental organizations working in the fields of environmental and rural development.
Keywords: Common lands